PERANCANGAN APLIKASI PENJUALAN KAYU BERBASIS WEB DENGAN MENGGUNAKAN METODE RATIONAL UNIFIED PROCESS (RUP) (STUDI KASUS: UD AMAN JAYA 3) - Tri Gunawan, Rio; Mulyana, Dadan; Dwicahya Supriatman, Rian (Fakultas Teknik Jurusan Sistem Informasi Universitas Galuh, 2025)
In the current era of globalization, digital technology has become a primary need in various activities and jobs, including in the corporate sector. Information systems are believed to be able to contribute to building competitive advantage through cost efficiency, improving quality and better service to consumers. This encourages companies to adopt digital technology, which is very helpful in effective decision making, both in small and large companies. The wood industry, as an important sector in the global economy, requires effective inventory and sales management. UD AMAN JAYA 3, a company operating in the wood trading sector, still uses a manual system in its inventory, purchasing and sales processes, which causes ineffectiveness in reporting and decision making. Therefore, to increase operational efficiency and effectiveness, it is proposed to develop a website-based timber sales information system. This system is expected to be able to store, process and present data in real-time, thereby supporting fast and precise decision making by marketing managers.